MACRO APPROACH IN NATIONAL EDUCATION SYSTEM - Rusdin; Moh. Ali (Paedagogia: Jurnal Pendidikan, 2020)
Macro approach in the national education is both organization empowering and education process. Education excuting organization has coverage and autonomous that it can accommodate society need in every situation. The education process is carried out openly to inlarge inputs from society. the education process is carried out by instilling a sense of excellence to face global challenges, while at the same time trying to make educational institutions the center of civilization. all that requires educational innovation that focuses on curriculum renewal, teaching materials, evaluation systems, building repairs and construction, etc. Teachers as education personnel have a central role in administering an education system. By becoming a teacher, someone expects to be able to obtain adequate compensation for the necessities of life. In motivation theory, the provision of appropriate rewards and punishments, can affect the performance and quality of work.